Implementation of the Four Pillars of Sustainable Tourism Destinations in the Tourism Village of Kampung Keranggan, South Tangerang - Hubner, Ira B.; Pramono, Rudy; Juliana, Juliana; Sitorus, Nova Bernedeta; Lemy, Diena M. (Budapest International Research and Critics University, 2022)
Tourism must be directed to truly realize capacity, equity, empowerment and sustainability in building communities. Especially in the era of the pandemic, with the new normal, it is hoped that tourism can become one of the pillars of people's lives. Kampung Keranggan, located in South Tangerang, is one of the tourist villages that has been recognized by the Ministry of Tourism and Creative Economy as being in the